Analyzing the Photoprotection Efficiency of Sunscreens Containing Antioxidants under Disinfection Conditions - Robert Sotler; Metka Adamič; Kristjan Jarni; Raja Dahmane; Polonca Trebše; Mojca Bavcon Kralj (MDPI AG, 2021)
Sunscreens ensure thorough protection against sunburn. The delivery of UV filters into the stratum corneum and viable epidermis could be reduced by the use of antioxidants (such as β-carotene and trans-resveratrol, alone or combined). The presence/absence of antioxidants (trans-resveratrol and β-carotene) in formulations containing benzophenone-3 (UV-filter) and their efficiency under disinfection and neutral conditions are studied and compared. The trial was conducted on 38 people. The prepared ointments were applied to the participants' forearms, irradiated and monitored by reflectance colorimetry after 0, 4, 6, and 8 min. Descriptive statistics were used to describe the skin color's main characteristics and the F-ratio was used to test overall differences. The ointments containing antioxidants and benzophenone-3 were the most efficient, followed by those with benzophenone-3 alone. It was proven that photoprotection with benzophenone-3 is still effective, despite the formation of its chlorinated products. Due to the short time of exposure to disinfecting conditions, it could be assumed that benzophenone-3 was only partially chlorinated. This clinical study demonstrated that formulations containing antioxidants are likely to be more suitable for protecting skin against UVB irradiation than a UV filter alone.